ANALISIS KESIAPAN DAN PENERIMAAN PENERAPAN APLIKASI INFINITY DENGAN TECHNOLOGY READINESS AND ACCEPTANCE MODEL (TRAM) PADA PT PGAS SOLUTION - Warda Nur Azizah (2022)
Technology is a medium used to support the business processes of companies and organizations. PT PGAS Solution has an innovative Inventory Information and Integration Activity (Infinity) application that is used to process the inventory system at PT PGAS Solution. The Infinity application is a relatively new application at PT PGAS Solution because before the arrival of the Infinity application, the inventory process was still using conventional methods. Before the Infinity application is ready to be implemented, Infinity application Users must be ready to implement the Infinity application. This study aims to measure the level of acceptance and application of Infinity Applications by testing the interrelationships of 10 Technology Readiness Acceptance Model (TRAM) variables, namely Optimism, Innovativeness, Insecurity, Discomfort, Perceived Usefulness, Perceived Ease of Use, and Intention to Use. This research is a quantitative research with data analysis method using Partial Least Square-Structural Equation Model (PLS-SEM). The output of this research is to provide recommendations that can be used to improve the readiness of Users and technology infrastructure at PT PGAS Solution in implementing the Infinity application. Based on the test results, the exogenous variable that has the highest influence is the Optimism (OPT) variable on the endogenous Perceived Usefulness (PU) variable. Both variables have a positive and significant effect of 45.5%.